Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Gunungsitoli - Bangun Teguh Putra; Sophia M. Kakisina; Maria M. Batee; Aferiaman Telaumbanua (Jurnal Ilmu Sosial Dan Politik, 2026)
This study aims to analyze the effect of service quality on community satisfaction at the Investment and One-Stop Integrated Service Office (DPMPTSP) of Gunungsitoli City. Service quality is one of the key factors determining the level of public satisfaction with government-provided services. High-quality services are expected to meet the needs and expectations of the community, thereby increasing public trust in public service institutions. This research employed a quantitative approach with an associative research design. The population consisted of community members who received services at DPMPTSP Gunungsitoli City. A total of 50 respondents were selected using the accidental sampling technique. Data were collected through questionnaires and analyzed using validity and reliability tests, Product Moment correlation analysis, coefficient of determination, simple linear regression, and hypothesis testing (t-test). The results indicate that service quality has a positive and significant effect on community satisfaction at DPMPTSP Gunungsitoli City. The correlation coefficient value of 0.467 shows a moderate relationship between service quality and community satisfaction. The coefficient of determination of 22% indicates that service quality explains 22% of the variation in community satisfaction, while the remaining 78% is influenced by other factors not examined in this study. Furthermore, the hypothesis test reveals that the calculated t-value (3.658) is greater than the t-table value (2.010) at a significance level of 5%, indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (H₀) is rejected. Based on these findings, it can be concluded that improving service quality, including tangible aspects, reliability, responsiveness, assurance, and empathy, can significantly enhance community satisfaction. Therefore, DPMPTSP Gunungsitoli City should continuously improve its service quality to provide more effective, efficient, and citizen-oriented public services.